First report of bacterial wilt of tomato (Solanum lycopersicum) caused by Ralstonia solanacearum in Benin - Sikirou, R.; Beed, Fenton D.; Ezin, V.; Gbehounou, G.; Miller, S.A.; Wydra, K. (Scientific Societies, 2009)
In June 2004, wilted tomatoes with no foliar yellowing were observed in Ouègbo, Atlantique District, Benin. The cut tomato stems released whitish bacterial ooze. Longitudinal sections of most stems showed brown vascular discoloration. Twenty symptomatic tomato plants were collected from 10 fields and exported to the Institute of Plant Disease and Plant Protection, Leibniz Universität Hannover, Germany. Bacteria were isolated on triphenyl tetrazolium chloride (TTC) medium (2) and three of the nine bacterial isolates that resembled Ralstonia solanacearum (colonies with red center and whitish periphery) and reference strain ToUdk (race 1 biovar 3; N. Thaveechai, Kasetsart University, Bangkok, Thailand) were used for pathogenicity tests. Five 4-week-old tomato plants cv. Tohounvi, grown in individual plastic pots (14 × 16 cm) containing sterilized field soil, were inoculated with each of the four isolates individually by soil drenching with 30 ml of the test cultures at 108 CFU/ml. Control plants were treated with 30 ml of sterile water. All plants were incubated in a glasshouse at 30°C. All plants inoculated with the isolates from Benin wilted 4 days after inoculation with symptoms similar to those observed in the field. Plants inoculated with the reference strain wilted 7 to 11 days after inoculation. Control plants treated with water remained healthy. R. solanacearum was recovered from the 20 symptomatic plants on TTC medium. The identity of the strains in comparison with the reference strain was confirmed by PCR with species-specific primers 759/760, which produced a single 281-bp fragment (3). Because similar symptoms were being increasingly reported by farmers across Benin and linked with reduced tomato yields, a disease survey was undertaken by IITA in 2006 and 2007. Wilted tomato plants were found across all agro-ecological zones of Benin (3 to 72% of plants per field). Isolates were recovered from the southeastern districts of Adja-Ouèrè, Sakété, Adjohoun, and Dangbo, the southwestern districts of Klouékanmè and Athiémé, the southern districts of Toffo and Bohicon, the central districts of Dassa and Savè, and the northern districts of Malanville and Karimama. Identification of R. solanacearum was confirmed following inoculation of tomato, production of characteristic wilting symptoms, recovery of the pathogen on TTC medium, and positive identification with ELISA kits (Pathoscreen Rs; Agdia Inc., Elkhart, IN). To our knowledge, this is the first report of R. solanacearum infecting tomato in Benin. Tomato is the most cultivated vegetable crop in Benin and important to the livelihood of many people in peri-urban and rural areas. Understanding that the cause of the observed crop losses is R. solanacearum may lead to implementation of management strategies such as deployment of disease-resistant cultivars or grafting tomatoes onto bacterial wilt-resistant rootstocks (1).References: (1) P. Aggarwal et al. Indian J. Agric. Sci. 78:379, 2008. (2) A. Kelman. Phytopathology 44:693, 1954. (3) N. Opina et al. Asian Pac. J. Mol. Biol. Biotechnol. 5:19, 1997.